Nilai-nilai Moral dalam Tradisi Ulur Antar pada Perkawinan Sarolangun Jambi - Hariandi, Ahmad; Nuraini, Renita; Putri, Cahya Yuliana Eka; Andayani, Nurlita; Inayah, Inayah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purposes of this paper are: (1) To describe the implementation of the community's traditional marriage ceremony in Sarolangun-Jambi Regency, (2) To describe what moral values are contained in the community's traditional marriage ceremony in Sarolangun-Jambi Regency. This research is a literature study. Data were collected by analyzing journals, scientific articles and literature reviews to achieve this goal. The research findings are as follows: 1) The implementation of the Ulur Antar tradition that occurs in Sarolangun-Jambi Regency, namely where the men bring offerings whose contents can be personal tools for the female candidate to household items for the two candidates. In this tradition, there is something that should not be forgotten, namely what is called the content of tafkir. The tafkir contains betel leaves which are tied in several parts, each bundle consisting of several sheets, then areca nut, and the ingredients used for betel nut. In addition, there is also nominal money that will be used as traditional money symbolically. If in the tafkir there is a nominal value of Rp. 20,000 then the customary money later from the men is Rp. 20,000,000, or with another nominal, 2) The moral values contained in the traditional marriages of the people of the Sarolangun-Jambi Regency include: a) Moral values related to God (Hablumminallah) are reflected in their implementation which interacted with religious teachings or beliefs in God Almighty. Almighty. In choosing the right mate, according to the religious demands adopted and based on the same religious belief, b) Social-related moral values (Hablumminannas) reflected in the stages of the traditional marriage ceremony of the Sarolangun-Jambi Regency community include: (1) Respecting others (2 ) Mutual cooperation (3) Strengthening Family Relations (4) Harmony (5) The form of preservation of customs in society (6) Respect, c) Individual Moral Values are moral values concerning oneself which are reflected in the traditional marriages of the people of Sarolangun-Jambi Regency, among others: (1) Responsibility (2) Application for blessing (3) Independence (4) Obedience (5) Willing to sacrifice.